S.N.U.F.F.: утопiя / В. О. Пелевин - Пелевин Виктор Олегович (Эксмо, 2012)
Фактическая дата выхода в свет: 2011 Экземпляры: ЦБ (20120626) / Инвентарный номер: 43991 / Цена: 232.38 / Авт.знак: П 24 / ББК: 84(2Рос=Рус)6